Local Waste Management as an Effort Increasing the Productivity of Fine Art Works - Osberth Sinaga; Azmi Azmi; Dionisius Sihombing (Universitas Negeri Medan, 2022)
This research wants to examine how the management of the creation of works of art made from organic waste (wood and marine biota) in Jaring Halus Village, North Sumatra. The method used in this study was the method of creation with an experimental model by utilizing waste as a model for creating works of art. The research was conducted in Jaring Halus Village, Langkat, North Sumatra. The stages in this research begin with identifying internal and external potentials. The internal potential is the location and organic waste such as waste wood and marine biota and the like. Furthermore, the external potential was the community's ability to explore the aesthetic power of waste to become an expression of works of art; in this case, presentations and design workshops are held through design simulations and references. The next step was selecting the quality of the waste wood, which includes elements of shape, structure, texture, and size. Based on the results of the research conducted, it can be concluded that some of the research findings are as follows: 1) the steps taken include: Planning, Mapping of waste locations, Mapping types of waste in categories, Understanding design as a material for creating works of art, Process of assembling forms works of art, the process of refining, the Process of presenting works of art. 2). In managing the creation of works of art by utilizing organic waste (wood and marine biota), we have produced several new prototypes of works of art made from organic waste. 3) Using creative methods based on adaptive and connotative patterns greatly encourages the creation of more significant and productive works of art.